A numerical approach of chaotic motions in a Duffing-Van der Pol oscillator - Dao, Nguyen Van; Dinh, Nguyen Van; Chi, Tran Kim; Dung, Nguyen (Vietnam Journal of Mechanics, 2007)
In the present paper the influence of the excitation frequency (\( u \)) and the forcing amplitude (\(e\)) on the chaotic behaviour of the system governed by equation